(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
The goal of this study was to see how effective Moringa oleifera leaf powder was at protecting male rat’s livers from hydroxychloroquine-induced liver damage. They were given dried Moringa leaf powder daily with meals orally for three weeks before being given different doses of hydroxychloroquine (1000, 500, and 250 mg / kg b.wt) daily for five days.In addition to the histology of the liver, the level of malondialdehyde (MDA), liver enzymes, and superoxide dismutase (SOD) enzyme activity were measured in the serum. The activity of liver enzymes and MDA increased when varied doses of hydroxychloroquine were given, but SOD activity decreased. Treatment with Moringa oleifera leaf powder lowers MDA levels and hepatic enzyme activity while increasing antioxidant enzyme activity.At the same time, the effects of hydroxychloroquine-induced tissue deterioration were improved when Moringa oleifera leaves were used. Finally, Moringa leaf powder increases antioxidant activity and reduces hydroxychloroquine-induced liver injury, suggesting that it could be used as a future liver injury prevention medication.